Study of Probiotic Effects of Bifidobacterium animalis subsp. lactis BB-12 and Lactobacillus plantarum 299v Strains on Biochemical and Morphometric Parameters of Rabbits after Obesity Induction - Assia Bouaziz; Amira Leila Dib; Nedjoua Lakhdara; Louiza Kadja; Elena Espigares; Elena Moreno; Omar Bouaziz; Mohammed Gagaoua (Biology, 2021)
This study aimed first to develop an experimental model of obesity and metabolic syndrome over 14 weeks using a diet called “cafeteria”, which is a high-fat diet, to evaluate its consequences on the biochemical and morphometric parameters in ITELV2006 strain rabbits. Second, the trial aimed to evaluate the effect of two strains of probiotics, these being Bifidobacterium animalis subsp. lactis BB-12® and Lactobacillus plantarum 299v®, on the obesity and MetS induced during the first experiment. Overall, the results of the “cafeteria” diet demonstrated significant changes in numerous biochemical and morphometric parameters, reproducing obesity and the main clinical manifestations of the metabolic syndrome in humans. The administration of the two probiotic strains demonstrated an impact on certain parameters of obesity and induced MetS. This study makes it possible to conclude that probiotics could be useful in the treatment of obesity and metabolic syndrome of rabbits, but in a dependent manner. Furthermore, this study evidenced the importance of selecting specific probiotic strains and dosages to achieve desirable results on rabbits or other species.